COMPLEX ASSESSMENT OF PHYSICAL DEVELOPMENT OF CHILDREN OF THE REPUBLIC OF TYVA - V. L. Gritsinskaya (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
The protection of physical health in rising generation has special significance under unfavorable demographic situation. Purpose: complex assessment of level of physical development of preschool children of the various ethnic groups living in the Republic of Tyva. Results of inspection of 1822 native children and 678 children of the alien population of the Republic of Tyva aged from 3 till 7 years are presented. The somatometry of preschool children is carried out (body length and body mass, thorax circle); the assessment of level and a harmony of physical development according to regional and interregional standards is given; methodic Ketle2 (BM1) and «stenii» indexes of Verveka-Vorontzov are used. We used the scheme for somatotypes definition by R.N. Dorohov and 1.1. Bahrah modified by 1.M. Vorontzov. 1t is established that the considerable part of the surveyed preschool children has disharmonious options of physical development. Among preschool children of the alien population the number of children with a length of a body exceeding age standards (32,6-26,5 %) is higher; among Tuvinians - with the low growth (18,5-22,7 %). Average physical development was revealed in 39,0-48,3 % at Tuvinians and 42,0-50,0 % children of the alien population according to the proportion of body mass to its length. Deficiency of weight of a body is registered more often at children of the alien population (12,5-22,2 %); the excess mass of a body is noted more often at Tuvinians (43,2-51,5 %). There is a big number of preschool children with high intensity of growth processes (dolichomorphia: 19,8- 29,2 % at Tuvinians and22,2-43,2 % children of the alien population) that allows to put them into the group of risk of probable decrease in resistance and working capacity. At the same time it is revealed that considerable part of children is defined to have a microsomatotype (23,2-26,1 % at Tuvinians and 22,2-29,9 % children of the alien population). For children ofindigenous people it can be ethnic feature of a constitution, but for children of the alien population probably it can be manifestation of complex influence of factors of environment. The most probable and operated factors promoting emergence of deviations in physical development, can be an irrational, unbalanced food and breaking of food behavior at children.